(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The educational goals of the subject should be developed based on the types of professional activities, special requirements, skills and knowledge presented in the professional description of the industry standard for each specialty. That is, standardized training programs should be fully compatible with network standards.